2009
DOI: 10.1215/15228517-2008-106
|View full text |Cite
|
Sign up to set email alerts
|

Lactate promotes glioma migration by TGF-β2–dependent regulation of matrix metalloproteinase-2

Abstract: Lactate dehydrogenase type A (LDH-A) is a key metabolic enzyme catalyzing pyruvate into lactate and is excessively expressed by tumor cells. Transforming growth factor-beta2 (TGF-beta2) is a key regulator of invasion in high-grade gliomas, partially by inducing a mesenchymal phenotype and by remodeling the extracellular matrix. In this study, we tested the hypothesis that lactate metabolism regulates TGF-beta2-mediated migration of glioma cells. Small interfering RNA directed against LDH-A (siLDH-A) suppresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(157 citation statements)
references
References 42 publications
9
148
0
Order By: Relevance
“…Although the molecular mechanisms are not clearly understood, lactate has been found to increase migration of various cancer cell lines (37,41). Recent data indicated that transforming growth factor beta (TGF-b) signaling pathway might be a mediator of the lactateassociated effects on migration of cancer cells (42). Moreover, lactate stimulates some cytokines, such as vascular endothelial growth factor (VEGF) and interleukin-8 (IL-8), resulting lactate-induced angiogenesis and increased tumor metastasis (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms are not clearly understood, lactate has been found to increase migration of various cancer cell lines (37,41). Recent data indicated that transforming growth factor beta (TGF-b) signaling pathway might be a mediator of the lactateassociated effects on migration of cancer cells (42). Moreover, lactate stimulates some cytokines, such as vascular endothelial growth factor (VEGF) and interleukin-8 (IL-8), resulting lactate-induced angiogenesis and increased tumor metastasis (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid was shown to induce both transcription and protein secretion of TGFβ2 in glioma cells [32] and to induce TGFβ1 production in in vivo model [33]. More recently, we found that an acidic microenvironment is able to promote TGFβ secretion and signaling in mesenchymal stem cells (MSC), driving the progression to malignancy in a melanoma cell system [34] and suggesting that acidity is a strong inducer of TGFβ family members.…”
Section: How Low Ph May Contribute To Dormancy Of Tumor Cells Aciditymentioning
confidence: 92%
“…Sev eral other metabo lites were also shown to in duce EMT. For in stance, lac tic acid was iden ti fied to be an ac ti va tor of TGF β2 path way in a glioma cell line [225]. More over, can cer cells un der go ing EMT ac cu mu late fatty acids that are taken up via CD36, in turn stim u lat ing Wnt and TGF β path ways [197].…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%